PENGARUH DOSIS PUPUK HAYATI Trichoderma sp. TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERUNG UNGU (Solanum mengolena L.) VARIETAS HIBRIDA - Putra Utama; Andree Saylendra; Rudi Gugum Gunawar (Jurnal Agroekoteknologi, 2015)
The aims of this study was to analyze the effects of biological fertilizers Trichoderma sp on the growth and yield of eggplant (Solanum melongena L.). The experiment used eggplant hybrid varieties and conducted in the village districts of Sekong village Rumingkang Cimanuk Pandeglang in Banten. Seven treatments of Trichoderma sp dose were tested in the experiment, namely 0g, 15g, 20g, 25g, 30g, 35g, and 40g / plant. The experiment used a randomized block design (RBD) and each treatment was repeated five times so that the total treatment unit was 35. Each polybag consisted of one plant. The results showed that the use of Trichoderma sp on various doses sp generate plant height, flower number, fruit number, fruit weight, fruit length, and dry weight was better than the plants that did not use the Trichoderma sp. The dose of Trichoderma sp was found best in T1 treatment with a dose of 15 grams/plant. Based on this study, further testing on Trichoderma sp. with higher dose and mixed with organic fertilizers is needed, as well as the need to do more research on plant diseases in eggplant (Solanum melongena L.).Key Words: Trichoderma sp., Biofertilizers, Purple eggplant